Hospital nurse staffing and patient outcomes in Chile: a multilevel cross-sectional study. Issue 8 (August 2021) - Aiken, Linda H; Simonetti, Marta; Sloane, Douglas M; Cerón, Consuelo; Soto, Paz; Bravo, David; Galiano, Alejandra; Behrman, Jere R; Smith, Herbert L; McHugh, Matthew D; Lake, Eileen T
Summary: Background: Unrest in Chile over inequalities has underscored the need to improve public hospitals. Nursing has been overlooked as a solution to quality and access concerns, and nurse staffing is poor by international standards. Using Chile's new diagnosis-related groups system and surveys of nurses and patients, we provide information to policy makers on feasibility, net costs, and estimated improved outcomes associated with increasing nursing resources in public hospitals. Methods: For this multilevel cross-sectional study, we used data from surveys of hospital nurses to measure staffing and work environments in public and private Chilean adult high-complexity hospitals, which were linked with patient satisfaction survey and discharge data from the national diagnosis-related groups database for inpatients. All adult patients on medical and surgical units whose conditions permitted and who had been hospitalised for more than 48 h were invited to participate in the patient experience survey until 50 responses were obtained in each hospital. We estimated associations between nurse staffing and work environment quality with inpatient 30-day mortality, 30-day readmission, length of stay (LOS), patient experience, and care quality using multilevel random-effects logistic regression models and zero-truncated negative binomial regression models, with clustering of patients within hospitals. Findings: We collected and analysed surveys of 1652 hospital nurses from 40 hospitals (34 public and six private), satisfaction surveys of 2013 patients, and discharge data for 761 948 inpatients. Nurse staffing was significantly related to all outcomes, including mortality, after adjusting for patient characteristics, and the work environment was related to patient experience and nurses' quality assessments. Each patient added to nurses' workloads increased mortality (odds ratio 1·04, 95% CI 1·01–1·07, p<0·01), readmissions (1·02, 1·01–1·03, p<0·01), and LOS (incident rate ratio 1·04, 95% CI 1·01–1·06, p<0·05). Nurse workloads across hospitals varied from six to 24 patients per nurse. Patients in hospitals with 18 patients per nurse, compared with those in hospitals with eight patients per nurse, had 41% higher odds of dying, 20% higher odds of being readmitted, 41% higher odds of staying longer, and 68% lower odds of rating their hospital highly. We estimated that savings from reduced readmissions and shorter stays would exceed the costs of adding nurses by US1·2 million and 5·4 million if the additional nurses resulted in average workloads of 12 or ten patients per nurse, respectively. Interpretation: Improved hospital nurse staffing in Chile was associated with lower inpatient mortality, higher patient satisfaction, fewer readmissions, and shorter hospital stays, suggesting that greater investments in nurses could return higher quality of care and greater value. Funding: Sigma Theta Tau International, University of Pennsylvania Global Engagement Fund, University of Pennsylvania School of Nursing's Center for Health Outcomes, and Policy Research and Population Research Center. Translation: For the Spanish translation of the abstract see Supplementary Materials section.